Shifting the focus: examining knowledge brokers' relational ecosystems - Caduff, Anita; Bornhaupt, L. Romina; Lockton, Marie; Rehm, Martin; Daly, Alan J. (Frontiers in Education, 2024)
Knowledge brokers are instrumental in improving education, including increasing equitable opportunities for all students. While many researchers have investigated the social networks between knowledge brokers and their audiences, less is known about knowledge brokers’ relational ecosystems, defined as partner networks with organizations and individuals for collaboration, support, and resource exchange. Therefore, the purpose of this study is to examine the characteristics of knowledge brokers’ relational ecosystems (e.g., size, strength of relationships, network closure) and how relational ecosystems support and shape knowledge creation and mobilization. This study uses egocentric social network analysis methods to analyze survey and interview data from six equity-focused and evidence-based knowledge broker organizations that create and mobilize resources to different levels of the education system, from K-12 schools to state-level policy contexts in the United States. The evidence suggests that participating knowledge brokers partnered with numerous and heterogeneous individuals and organization types, including researchers, leaders, foundations, and intermediaries. The core relational ecosystems were characterized by strong relationships, partly driven by individual team members’ social networks and comprising micro-networks, and were well-connected (i.e., network closure). Furthermore, our data indicates that beyond being collaborators, partners provided infrastructure and financial resources, served as intermediaries for knowledge mobilization, provided insights into policy contexts and audiences’ needs, supported knowledge brokers’ capacity building, and connected knowledge brokers to people and organizations. These relationships were not one-directional, but often mutually beneficial, resulting in reciprocated relational ecosystems. Our findings suggest that it might be beneficial for knowledge brokers to strategically cultivate relational ecosystems by supporting individual team members in cultivating their social networks, adapting to evolving needs and challenges while being conscious of long-term priorities, and balancing strong ties with the (re-)engagement with new partners and different sources of information.